An Implementation of POPBL for Analog Electronics (BEL10203) Course at the Faculty Of Electrical and Electronic Engineering, Uthm - Mohamed, Masnani; Mat Jubadi, Warsuzarina; Wan Zaki, Suhaimizan (Journal of Technical Education and Training, 2011)
A Project Oriented Problem Based Learning (POPBL) has been introduced to the first year students in the Analog Electronics (BEL10203) course at the Faculty of Electrical and Electronic Engineering, UTHM. The aim is to design an electronic circuit using transistors and diodes that can function as electronic appliances with low cost, low power consumption, and has the features of smart and portable. The total of 143 students were divided into groups and assigned to setup an electronic based company that will be manufacturing the electronic product. Each group had to conduct their regular meetings and develop different kind of products with their creativity. The overall evaluation is divided for both lecturer and peer assessment which carried 20% of their course work. The assessment covered 60% of evaluation for the group management, attitude, progress presentation, report writing while another 40% for the functionality and features of their product. As a result, the POPBL session has increased the student’s ability to analyze and design an analog circuit using various kinds of transistors and diodes. They also gained practical understanding on transistor and diode operation. The POPBL not only expanded their experience in using software tools for circuit design and simulation, but also developed greater awareness to conduct professional presentation and technical report. They also learned to work as professional, keen to ethical responsibilities and committed to the group. The analysis conducted has shown that 95% of the students agreed that the problem given helped them understands better the course syllabus and developed a good problem solving skills.